The Cyclical Behavior of Job Creation and Job Destruction - Dale Mortensen; Christopher Pissarides (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
Panel studies show that job creation and job destruction coexist at all phase of the business cycle. In this paper, we develop a model of endogenous job destruction in response to persistent idiosyncratic shocks and incorporate the model into he transactions cost (matching) approach to equilibrium job creation and wage determination. Second, we examine the dynamic stochastic implications of the model for co-movement between job creation, job destruction, and the employment growth induced by a common aggregate shock to productivity. Finally, a simulation of the model for a reasonable parametrization demonstrates that it can explain cyclical properties of US Manufacturing data.
Keywords: 330